EFEKTIVITAS PENGGUNAAN KARTU MENUJU GIGI SEHAT ELEKTRONIK (e-KMGS) TERHADAP PERAN DAN MOTIVASI IBU UNTUK KESEHATAN GIGI ANAK - Wijaya, Dhandi; Marlindayanti, Marlindayanti; Vani, Refi Mutiara (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Palembang, 2024)
The average caries prevalence of the Indonesian population aged 3-4 years with dental and oral problems is 81.5% with the highest percentage being 96.8% at the age of 55-64 years. This shows that the percentage of dental and oral problems at the age of 3-4 years has entered quite high numbers. Participation and attention from parents is what preschool aged children need. The reality is that children's dental health receives little attention from parents with the assumption that children's teeth will be replaced by permanent teeth. Many cases of caries today are caused by a lack of role and knowledge of parents regarding choosing the right type of food and dental care for their children, especially pre-school age children. This research aims to determine the effectiveness of e-KMGS as a medium in increasing the role and motivation of mothers for children's dental health. This research is quantitative research with a quasi-experimental research design. The sample in this research was taken using purposive sampling. The results of this research show that the average mother's role before e-KMGS assistance is 37.3 and the average mother's motivation before e-KMGS assistance is 28.5. The average mother's role after e-KMGS assistance was 91.6 and the average mother's motivation after e-KMGS assistance was 44.9. The average difference before and after using e-KMGS role is 54.3 and motivation is 16.4. The conclusion is that the use of e-KMGS as a media is significantly effective in increasing the role and motivation of mothers for children's dental health.